2006
DOI: 10.1073/pnas.0602384103
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism to signal receptor–substrate interactions with luminescent quantum dots

Abstract: Semiconductor quantum dots are becoming valuable analytical tools for biomedical applications. Indeed, their unique photophysical properties offer the opportunity to design luminescent probes for imaging and sensing with unprecedented performance. In this context, we have identified operating principles to transduce the supramolecular association of complementary receptor-substrate pairs into an enhancement in the luminescence of sensitive quantum dots. Our mechanism is based on the electrostatic adsorption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(111 citation statements)
references
References 49 publications
1
106
1
1
Order By: Relevance
“…A common method for FRET-based sensing of an analyte involves the displacement of a bound quencher. [81] For example, the association of maltose to the hybrid composed of the maltose-binding protein was examined by the application of a CdSe/ZnS QD linked to the maltose binding protein (MBP). [39] These particles were interacted with a b-cyclodextrin-QSY-9 dye conjugate, resulting in the quenching of the QDs luminescence (Figure 8 A).…”
Section: Water Solubilization and Functionalization Of Quantum Dots Wmentioning
confidence: 99%
“…A common method for FRET-based sensing of an analyte involves the displacement of a bound quencher. [81] For example, the association of maltose to the hybrid composed of the maltose-binding protein was examined by the application of a CdSe/ZnS QD linked to the maltose binding protein (MBP). [39] These particles were interacted with a b-cyclodextrin-QSY-9 dye conjugate, resulting in the quenching of the QDs luminescence (Figure 8 A).…”
Section: Water Solubilization and Functionalization Of Quantum Dots Wmentioning
confidence: 99%
“…11 In addition to sensing configurations that use hole accepting metal complexes to quench QD PL, there are examples that use electron accepting molecules, such as quinones, to monitor enzyme activity 199,200 and intracellular pH, 183 or bipyridinium, to monitor receptor-substrate interactions. 180 Initially, Yildiz et al electrostatically adsorbed a bipyridinium dye to the surface of QDs and found that a macrocyclic receptor, cucurbit [7]uril, could disrupt the CT quenching interaction through competitive host-guest interactions. 180 Cui et al reversed this approach by modifying CdTe QDs with thiolated cucurbit [6]uril (CB [6]) via self-assembly.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 99%
“…180 Initially, Yildiz et al electrostatically adsorbed a bipyridinium dye to the surface of QDs and found that a macrocyclic receptor, cucurbit [7]uril, could disrupt the CT quenching interaction through competitive host-guest interactions. 180 Cui et al reversed this approach by modifying CdTe QDs with thiolated cucurbit [6]uril (CB [6]) via self-assembly. 201 The CB [6] improved the colloidal stability of the QDs and, more pertinently, bound a nitrobenzene amine electron acceptor through a host-guest interaction, providing the proximity needed for CT quenching.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 99%
“…14) Through combining with receptors such as proteins or DNA and detachment from the QD surface, the PL intensity was partially recovered and the amount of PL peak intensity was used as a measure of glucose concentration. 15,16) In this study, we report another effective design of PL glucose biosensors using CdSe/ZnS QDs, organic acid and glucose oxidase (GOx). We measured the increase in the PL peak intensity through the transfer of electrons occurring during the enzymatic oxidation reaction to the conduction band of the QDs.…”
Section: -8)mentioning
confidence: 99%